Parametrli kórsetkishli teńlemeler hám teńsizliklerdi sheshiw usılları - Djumabaev, N; Kuanıshbaev, T (SCIENCE and SOCIETY, 2022)
The article presents various methods of parametric exponential equations and the inequality.
Keywords: parameter; exponential equations; parametric exponential inequalities